2020
DOI: 10.3390/su12051913
|View full text |Cite
|
Sign up to set email alerts
|

Saline and Alkaline Tolerance of Wetland Plants—What are the Most Representative Evaluation Indicators?

Abstract: The increasing discharge of wastewater containing inorganic salts, sometimes accompanied by high pH, has been a worldwide environmental problem. Constructed wetlands (CWs) are considered a viable technology for treating saline and/or alkaline wastewater provided that saline-alkaline tolerant plant species are selected and applied. The influence of both saline and alkaline stress on four wetland plant species during their seed germination, early growth, vegetative propagation and continued growth stages was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Seedling growth shoot height and root length were the most sensitive to salt stress [11]. Salinity stress decrease the leaf size, internode, and length leading to the stunted growth of salt marsh and sand-dune plants [21].…”
Section: Effect Of Salinity On Plant Growthmentioning
confidence: 99%
“…Seedling growth shoot height and root length were the most sensitive to salt stress [11]. Salinity stress decrease the leaf size, internode, and length leading to the stunted growth of salt marsh and sand-dune plants [21].…”
Section: Effect Of Salinity On Plant Growthmentioning
confidence: 99%
“…Spatial soil nutrient gradients have been widely reported to shape the distribution and composition of wetland vegetation communities (Graham & Mendelssohn, 2016;Ma et al, 2021;Zheng et al, 2019), and unsurprisingly, we found that soil organic carbon, nitrogen, and pH, three variables closely related to soil nutrient availability to wetland plants, were the most important soil factors to species suitability in wetlands. Specifically, nitrogen is the predominant limiting nutrient that regulates plant growth and productivity of wetland ecosystems (Bai et al, 2012;Mitsch & Gosselink, 2015;Olde Venterink et al, 2001), and pH not only impacts directly on plant physiological processes, but also influences the availability and toxicity of certain critical elements for wetland plants, such as phosphorus, potassium, iron, and sulfur (Cheng et al, 2020;Mitsch & Gosselink, 2015;Tercero et al, 2015). Moreover, compared to nonwoody species, woody species were more affected by soil nitrogen, reflecting the relatively high nutrient uptake of woody species in wetlands (Goodwillie et al, 2020;Holmgren et al, 2015;Laiho, 2006;Macrae et al, 2013).…”
Section: The Influence Of Abiotic Factors and Anthropogenic Disturban...mentioning
confidence: 99%
“…Saline–alkaline soils are characterized by both high sodium ion (Na + ) concentration and high pH, which cause more complex stress effects on plants than pH‐neutral saline soils (Tang et al ., 2014 ). To survive, plants growing in saline–alkaline soils have to cope with both physiological drought and Na + toxicity, in addition to the cellular damage induced by high pH (Cheng et al ., 2020 ; Liu et al ., 2010 ). Rice ( Oryza sativa L.) serves as a staple food crop for more than half of the world population (Gross and Zhao, 2014 ) and as a model monocot for bioenergy research (Izawa and Shimamoto, 1996 ).…”
Section: Introductionmentioning
confidence: 99%